When van Mechelen's sequence of injury prevention model requires pragmatic and accelerated action: the case of para alpine skiing in Pyeong Chang 2018 - Blauwet, C.; Webborn, N.; Kissick, J.; Lexell, J.; Stomphorst, J.; van de Vliet, P.; Lazarovski, D.; Derman, W. (British Journal of Sports Medicine, 2019)
Results of the Paralympic Injury and Illness Surveillance Study noted an unusually high injury incidence rate (IR) in the sport of Para alpine skiing at the 2014 Sochi Paralympic Games (IR 48.3, a sixfold increase in acute injuries in comparison to the Vancouver 2010 Paralympic Games).1-3 There were likely several associated factors. Some were clearly modifiable such as the course design, number of training runs permitted on the course and the command and control structure between the technical and medical staff. Additionally, Paralympic officials recognised that careful monitoring of weather data and timely management of snow production, taking advantage of modern technology, had the potential to reduce injury risk. Thus, for the 2018 PyeongChang Paralympic Winter Games (the Games), the International Paralympic Committee (IPC) Medical Committee, in collaboration with the World Para Alpine Skiing (WPAS) sport technical staff, implemented a series of changes following Professor Willem van Mechelen`s `Sequence of (Injury) Prevention` model4: